PENGARUH PELATIHAN, KEJELASAN TUJUAN DAN DUKUNGAN PIMPINAN TERHADAP EFEKTIVITAS SISTEM AKUNTANSI KEUANGAN DAERAH (STUDI PADA BADAN KEUANGAN KABUPATEN NGAWI) - Ningsih, Hayu Wulan; Rispantyo, Rispantyo; Kristianto, Djoko (Universitas Slamet Riyadi, 2021)
This research aims to test the influence (1) of Training (2) Clarity ofObjectives (3) leadership support on the effectiveness of regional financialaccounting systems. This study uses primary data obtained by deployingquestionnaires to potential respondents. The population in this study is Ngawifinancial agency. The sampling techniques in this study used purposive samplingmethods. The data analysis techniques used in this study are descriptive analysistests, data quality tests, classic assumption tests and hypothesis tests(determination coefficients, F tests and t tests). Based on the results of dataanalysis of the influence of training, clarity of objectives and support of superiorshas a positive and significant effect on the effectiveness of the regional financialaccounting system. To improve the effectiveness of the regional financialaccounting system, then all parties in the agency need to be aware of theimportance of the regional financial accounting system and need to increase thesupport of leaders who fully support in realizing the effectiveness of the regionalfinancial accounting system better in an institution. The advice in this study is toexpand the research object to government agencies, use longer research timespans and add variables in subsequent research.